A sodium ion positive electrode material capable of realizing rapid charging and discharging, a preparation method thereof, and a sodium ion battery

Through the design of sodium ion positive electrode material with multi-layer structure, different sintering processes are used to form a tight core and stable intermediate layer, combined with the outer layer supplemented by lithium salt/sodium salt, the problem of large resistance to embedding and removal of the positive electrode material of sodium ion battery is solved, and the problem of large resistance to detachment of sodium ion battery positive electrode material is achieved. Fast charging and discharging and high energy density effects.

CN115377380BActive Publication Date: 2024-12-13DONGGUAN CHAM BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210994218.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-18
Publication Date
2024-12-13
Estimated Expiration
2042-08-18

AI Technical Summary

Technical Problem

The sodium ion radius in the positive electrode material of sodium ion batteries is large, resulting in a large resistance to the positive electrode embedded and discharge, which is not suitable for large-scale charging and discharging applications.

Method used

Using a multi-layer structure of sodium ion positive electrode material, the core layer, the intermediate layer and the outer layer are successively formed from the inside to the outside, and a tight core structure, stable intermediate layer and lithium salt/sodium salt supplementation are formed through sintering processes of different temperatures and times. The outer layer improves the compressive resistance and electrochemical properties of the material.

Benefits of technology

It realizes the fast charging and discharging capacity of sodium ion batteries, improves energy density and first-term efficiency, meets the demand for multiplying charge and discharge, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003804965320000101
    Figure BDA0003804965320000101
  • Figure HDA0003804965330000011
    Figure HDA0003804965330000011
  • Figure HDA0003804965330000012
    Figure HDA0003804965330000012
Patent Text Reader

Abstract

The present invention provides a sodium ion positive electrode material capable of rapid charge and discharge, which has a multilayer structure, and is composed of a core layer, an intermediate layer, and an outer layer from the inside to the outside. The positive electrode material in the present invention has a multilayer structure with a gradient from the inside to the outside, and the inner core is sintered at a low temperature to form a compact core structure with few defects, which can improve the compressive resistance of the material. The intermediate layer is sintered at a high temperature, and the solid phase reaction between particles forms a stable crystal form. By controlling the time and controlling the grain size, the production of positive electrodes with the required grain size can be achieved. The third layer, i.e., the outermost particle surface layer, is supplemented with lithium salt and sodium salt, and sintered again to improve the initial efficiency and service life of the material. The present invention also provides a method for preparing a sodium ion positive electrode material capable of rapid charge and discharge and a sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion positive electrode material capable of realizing rapid charging and discharging, a preparation method thereof, and a sodium ion battery. Background Art

[0002] Sodium-ion batteries have the characteristics of extensive resources, low price, safety and reliability, and can also meet the requirements of electrochemical performance indicators such as energy and power density. They are suitable for large-scale energy storage applications and are an emerging hotspot in the field of advanced energy storage technology. However, the radius of sodium ions in the positive electrode materials of sodium-ion batteries is large, and the resistance to the insertion and removal of the positive electrode is large, which cannot be applied to the needs of high-rate charge and discharge applications. Summary of the invention

[0003] The object of the present invention is to provide a sodium ion positive electrode material capable of achieving rapid charge and discharge, a preparation method thereof and a sodium ion battery. The positive electrode material in the present invention has high energy density, high initial efficiency and can achieve the requirements of rate charge and discharge.

[0004] The present invention provides a sodium ion positive electrode material capable of realizing rapid charge and discharge, which has a multilayer structure, and comprises a core layer, an intermediate layer and an outer layer from the inside to the outside;

[0005] The chemical formula of the core layer is: Na x1 [Li y1 (Ni a1 Fe b1 Mn c1 ) z1 ]O2 formula I; 0.8≤x1<0.85, 0≤y1≤0.05, 0.95≤z1≤1; y1+z1=1; 0.15≤a1≤0.4; 0.15≤b1≤0.4; 0.4≤c1≤0.8; a1+b1+c1=1;

[0006] The chemical formula of the intermediate layer is: Na x2 [Li y2 (Ni a2 Fe b2 Mn c2 ) z2 ]O2 formula II; 0.8≤x2<1, 0.03≤y2≤0.07, 0.93≤z2≤0.97; y2+z2=1; 0.15≤a2≤0.4; 0.15≤b2≤0.4; 0.4≤c2≤0.8; a2+b2+c2=1;

[0007] The chemical formula of the outer layer is: Na x3 [Li y3 (Ni a3 Fe b3 Mn c3 )z3 ]O2 formula III; 0.8≤x3<1, 0.05≤y3≤0.1, 0.9≤z3≤0.95; y3+z3=1; 0.15≤a3≤0.4; 0.15≤b3≤0.4; 0.4≤c3≤0.8; a3+b3+c3=1.

[0008] Preferably, the sodium ion positive electrode material capable of achieving rapid charge and discharge is an O3 phase material.

[0009] Preferably, the sodium ion positive electrode material capable of achieving rapid charge and discharge has a chemical formula shown in Formula IV:

[0010] Na x [Li y (Ni a Fe b Mn c ) z ]O2 Formula IV;

[0011] Among them, 0.8≤X<1; y≤0.1; 0.9≤z≤1; y+z=1; 0.15≤a≤0.4; 0.15≤b≤0.4; 0.4≤c≤0.8; a+b+c=1.

[0012] The present invention provides a method for preparing a sodium ion positive electrode material capable of achieving rapid charge and discharge as described above, comprising the following steps:

[0013] A) Sodium source, lithium source, nickel source, iron source and manganese source are mixed according to Na x1 [Li y1 (Ni a1 Fe b1 Mn c1 ) z1 ] The stoichiometric ratio of the raw materials is uniformly mixed in O2, and a sintering is performed under a protective atmosphere to obtain a core layer;

[0014] B) According to Na x2 [Li y2 (Ni a2 Fe b2 Mn c2 ) z2 ]O2 is added with a sodium source, a lithium source, a nickel source, an iron source and a manganese source in a stoichiometric ratio, and secondary sintering is performed under a protective atmosphere to obtain an intermediate layer;

[0015] C) According to Na x3 [Li y3 (Ni a3 Fe b3 Mn c3 ) z3]A sodium source, a lithium source, a nickel source, an iron source and a manganese source are added in a stoichiometric ratio of O2, and sintered three times under a protective atmosphere to obtain a sodium ion positive electrode material that can achieve fast charge and discharge.

[0016] Preferably, the primary sintering temperature is 200-500° C.; and the primary sintering time is 5-10 hours.

[0017] Preferably, the temperature of the secondary sintering is 600-1500° C., and the time of the secondary sintering is 2-10 hours.

[0018] Preferably, the temperature of the three sintering processes is 500-1000° C., and the time of the three sintering processes is 3-8 hours.

[0019] Preferably, the sodium source is one or more of sodium hydroxide, sodium carbonate, sodium chloride, sodium sulfate, sodium nitrate and sodium acetate;

[0020] The lithium source is one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium sulfate, lithium nitrate and lithium acetate;

[0021] The nickel source is one or more of nickel hydroxide, nickel carbonate, nickel sulfate, nickel nitrate, nickel acetate, and nickel oxalate;

[0022] The iron source is one or more of iron powder, ferric chloride, ferric nitrate, ferric sulfate, ferric oxide, ferrous oxide, etc.;

[0023] The manganese source is one or more of manganese hydroxide, manganese carbonate, manganese sulfate, manganese nitrate, manganese acetate and manganese oxalate.

[0024] Preferably, the protective atmosphere is one or more of nitrogen, helium and argon.

[0025] The present invention provides a sodium ion battery, comprising the sodium ion positive electrode material capable of achieving rapid charge and discharge as described above or the sodium ion positive electrode material capable of achieving rapid charge and discharge obtained by the preparation method described above.

[0026] The present invention provides a sodium ion positive electrode material capable of realizing rapid charge and discharge, which has a multilayer structure, and comprises a core layer, an intermediate layer and an outer layer from the inside to the outside; the chemical formula of the core layer is: Na x1 [Li y1 (Ni a1 Fe b1 Mn c1 ) z1]O2 formula I; 0.8≤x1<0.85, 0≤y1≤0.05, 0.9≤z1≤1; y1+z1=1; 0.15≤a1≤0.4; 0.15≤b1≤0.4; 0.4≤c1≤0.8; a1+b1+c1=1; the chemical formula of the intermediate layer is: Na x2 [Li y2 (Ni a2 Fe b2 Mn c2 ) z2 ]O2 formula II; 0.8≤x2<1, 0.03≤y2≤0.07, 0.9≤z2≤1; y2+z2=1; 0.15≤a2≤0.4; 0.15≤b2≤0.4; 0.4≤c2≤0.8; a2+b2+c2=1; the chemical formula of the outer layer is: Na x3 [Li y3 (Ni a3 Fe b3 Mn c3 ) z3 ]O2 0.8≤x3<1, 0.05≤y3≤0.1, 0.9≤z3≤1; y3+z3=1; 0.15≤a3≤0.4; 0.15≤b3≤0.4; 0.4≤c3≤0.8; a3+b3+c3=1. The positive electrode material in the present invention has a multi-layer structure with a gradient from the inside to the outside. The inner core is sintered at a low temperature to form a compact core structure with few defects, which can improve the compressive resistance of the material; the middle layer is sintered at a high temperature, and the solid phase reaction between the particles forms a stable crystal form. By controlling the time to control the grain size, the production of positive electrodes with the required grain size can be achieved. The third layer, i.e., the outermost particle surface layer, is supplemented with lithium salt and sodium salt, and sintered again to improve the initial efficiency and service life of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0028] Figure 1 is the charge and discharge curve of the sodium ion battery obtained in Example 1 of the present invention under 0.2C conditions;

[0029] Figure 2 This is the cycle curve of the sodium ion battery obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The present invention provides a sodium ion positive electrode material capable of realizing rapid charge and discharge, which has a multilayer structure, and comprises a core layer, an intermediate layer and an outer layer from the inside to the outside;

[0031] The chemical formula of the core layer is: Na x1 [Li y1 (Ni a1 Fe b1 Mn c1 ) z1 ]O2 formula I; 0.8≤x1<0.85, 0≤y1≤0.05, 0.95≤z1≤1; y1+z1=1; 0.15≤a1≤0.4; 0.15≤b1≤0.4; 0.4≤c1≤0.8; a1+b1+c1=1;

[0032] The chemical formula of the intermediate layer is: Na x2 [Li y2 (Ni a2 Fe b2 Mn c2 ) z2 ]O2 formula II; 0.8≤x2<1, 0.03≤y2≤0.07, 0.93≤z2≤0.97; y2+z2=1; 0.15≤a2≤0.4; 0.15≤b2≤0.4; 0.4≤c2≤0.8; a2+b2+c2=1;

[0033] The chemical formula of the outer layer is: Na x3 [Li y3 (Ni a3 Fe b3 Mn c3 ) z3 ]O2 0.8≤x3<1, 0.05≤y3≤0.1, 0.9≤z3≤0.95; y3+z3=1; 0.15≤a3≤0.4; 0.15≤b3≤0.4; 0.4≤c3≤0.8; a3+b3+c3=1.

[0034] In the present invention, 0.8≤x1<0.85, such as x1 is 0.8, 0.81, 0.82, 0.83, 0.84, preferably a range value with any of the above values ​​as the upper or lower limit; 0≤y1≤0.05, such as y1 is 0, 0.01, 0.02, 0.03, 0.04, 0.05, preferably a range value with any of the above values ​​as the upper or lower limit; 0.95≤z1≤1, such as z1 is 0.95, 0.96, 0.97, 0.98, 0.99, 1, preferably a range with any of the above values ​​as the upper or lower limit; 0.15≤a1≤0.4, such as a1 is 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0. 31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, preferably a range with any of the above values ​​as the upper or lower limit; 0.15≤b1≤0.4, such as b1 is 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0 .27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, preferably a range value with any of the above values ​​as the upper or lower limit; 0.4≤c1≤0.8, such as c1 is 0.4, 0.5, 0.6, 0.7, 0.8, preferably a range value with any of the above values ​​as the upper or lower limit.

[0035] In the present invention, 0.8≤x2<1, such as x2 is 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, preferably a range value with any of the above values ​​as the upper or lower limit; 0.03≤y2≤0.07, such as y2 is 0.03, 0. 0.4, 0.05, 0.06, 0.07, preferably a range with any of the above values ​​as the upper or lower limit; 0.93≤z2≤0.97, such as z2 is 0.93, 0.94, 0.95, 0.96, 0.97, preferably a range with any of the above values ​​as the upper or lower limit; 0.15≤a2≤0.4, such as a2 is 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, preferably a range with any of the above values ​​as the upper or lower limit; 0.15≤b2≤0.4, such as b2 is 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.2 3, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, preferably a range value with any of the above values ​​as the upper or lower limit; 0.4≤c2≤0.8, such as c2 is 0.4, 0.5, 0.6, 0.7, 0.8, preferably a range value with any of the above values ​​as the upper or lower limit.

[0036] In the present invention, 0.8≤x3<1, such as x3 is 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, preferably a range value with any of the above values ​​as the upper or lower limit; 0.05≤y3≤0.1, such as y3 is 0.05, 0.06 , 0.07, 0.08, 0.09, 0.1, preferably a range with any of the above values ​​as the upper or lower limit; 0.9≤z3≤0.95, such as z3 is 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, preferably a range with any of the above values ​​as the upper or lower limit; 0.15≤a3≤0.4, such as a3 is 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0. 23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, preferably a range with any of the above values ​​as the upper or lower limit; 0.15≤b3≤0.4, such as b3 is 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0 .23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, preferably a range value with any of the above values ​​as the upper or lower limit; 0.4≤c3≤0.8, such as c3 is 0.4, 0.5, 0.6, 0.7, 0.8, preferably a range value with any of the above values ​​as the upper or lower limit.

[0037] The present invention selects O3 phase materials with a Na content greater than 0.8, and x (Ni a Fe b Mn c ) y O2, Li ion doping is performed to further improve the performance of the material. However, when the Na content is X=1, Na(Ni a Fe b Mn c ) y O2. The material is prone to phase change. Therefore, in the sodium ion positive electrode material in the present application, 0.8≤X<1, it has the chemical formula shown in Formula IV:

[0038] Na x [Li y (Ni aFe b Mn c ) z ]O2 Formula IV;

[0039] In formula IV, 0.8≤x<1; y≤0.1; 0.9≤z≤1; y+z=1; 0.15≤a≤0.4; 0.15≤b≤0.4; 0.4≤c≤0.8; a+b+c=1.

[0040] In the present invention, 0.8≤x<1, such as x is 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, preferably a range value with any of the above values ​​as the upper or lower limit; y≤0.1, such as y is 0, 0.01, 0.02, 0.03, 0.04, 0. 0.5, 0.06, 0.07, 0.08, 0.09, 0.1, preferably a range with any of the above values ​​as the upper or lower limit; 0.9≤z≤1, such as z is 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, preferably a range with any of the above values ​​as the upper or lower limit; 0.15≤a≤0.4, such as a is 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, preferably a range with any of the above values ​​as the upper or lower limit; 0.15≤b≤0.4, such as b is 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.2 1, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, preferably a range value with any of the above values ​​as the upper or lower limit; 0.4≤c≤0.8, such as c is 0.4, 0.5, 0.6, 0.7, 0.8, preferably a range value with any of the above values ​​as the upper or lower limit.

[0041] The present invention also provides a method for preparing a sodium ion positive electrode material capable of achieving rapid charge and discharge, comprising the following steps:

[0042] A) Sodium source, lithium source, nickel source, iron source and manganese source are mixed according to Na x1 [Li y1 (Nia1 Fe b1 Mn c1 ) z1 ] The stoichiometric ratio of the raw materials is uniformly mixed in O2, and a sintering is performed under a protective atmosphere to obtain a core layer;

[0043] B) According to Na x2 [Li y2 (Ni a2 Fe b2 Mn c2 ) z2 ]O2 is added with a sodium source, a lithium source, a nickel source, an iron source and a manganese source in a stoichiometric ratio, and secondary sintering is performed under a protective atmosphere to obtain an intermediate layer;

[0044] C) According to Na x3 [Li y3 (Ni a3 Fe b3 Mn c3 ) z3 ]A sodium source, a lithium source, a nickel source, an iron source and a manganese source are added in a stoichiometric ratio of O2, and sintered three times under a protective atmosphere to obtain a sodium ion positive electrode material that can achieve fast charge and discharge.

[0045] In the present invention, the sodium source in the primary sintering, secondary sintering and tertiary sintering can be independently selected from one or more of sodium hydroxide, sodium carbonate, sodium chloride, sodium sulfate, sodium nitrate and sodium acetate; the lithium source in the primary sintering, secondary sintering and tertiary sintering can be independently selected from one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium sulfate, lithium nitrate and lithium acetate; the nickel source in the primary sintering, secondary sintering and tertiary sintering can be independently selected from one or more of nickel hydroxide, nickel carbonate, nickel sulfate, nickel nitrate, nickel acetate and nickel oxalate; the iron source in the primary sintering, secondary sintering and tertiary sintering can be independently selected from one or more of iron powder, ferric chloride, ferric nitrate, ferric sulfate, ferric oxide, ferrous oxide and the like.

[0046] In the present invention, the protective atmosphere used in the primary sintering, the secondary sintering and the tertiary sintering can be independently selected from one or more of nitrogen, helium and argon.

[0047] In the present invention, the raw materials in the core layer, i.e., the primary sintering, are preferably prepared according to the stoichiometric ratio in Formula I.

[0048] In the present invention, the temperature of the primary sintering is preferably 200-500°C, more preferably 300-400°C, such as 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, preferably a range value with any of the above values ​​as the upper or lower limit; the time for the first sintering is preferably 5 to 10 hours, more preferably 6 to 9 hours, such as 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, preferably a range value with any of the above values ​​as the upper or lower limit; the present invention obtains a core layer structure with good structural stability and few crystal development defects through a low-temperature slow sintering process and by controlling the combination of temperature and time.

[0049] In the present invention, the raw materials in the intermediate layer, i.e., the secondary sintering, are preferably mixed according to the stoichiometric ratio in Formula II.

[0050] In the present invention, the temperature of the secondary sintering is preferably 600-1500°C, more preferably 700-1200°C, such as 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, preferably a range value with any of the above numerical values ​​as the upper or lower limit; the time of the secondary sintering is preferably 2-10 hours, more preferably 3-8 hours, such as 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, preferably a range value with any of the above numerical values ​​as the upper or lower limit; the present invention adjusts the temperature and time control according to the grain size requirements of the final product, and sintering at high temperature forms the main active part of the product.

[0051] In the present invention, the raw materials in the outermost layer, i.e., the third sintering, are preferably mixed according to the stoichiometric ratio in formula III.

[0052] In the present invention, the temperature of the three sinterings is preferably 500-1000°C, more preferably 600-900°C, such as 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, preferably a range value with any of the above values ​​as the upper or lower limit; the time of the three sinterings is preferably 3-8 hours, more preferably 4-6 hours, such as 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, preferably a range value with any of the above values ​​as the upper or lower limit; the present invention performs granulation and shaping according to the particle size requirements of the final product, and further sintering to complete the preparation of the sodium ion positive electrode material, and the stability of the metal transition layer is achieved by introducing the stability of the lithium support structure in the multi-layer transition metal layer.

[0053] After three solid-phase sintering steps, the obtained sodium ion positive electrode material has a three-layer structure of tight-loose-tight, and each layer has a different chemical formula. It has high energy density, high initial efficiency, and can meet the requirements of rate charging and discharging.

[0054] The present invention also provides a sodium ion battery, comprising the sodium ion positive electrode material capable of achieving rapid charge and discharge as described above.

[0055] The present invention provides a sodium ion positive electrode material capable of realizing rapid charge and discharge, which has a multilayer structure, and comprises a core layer, an intermediate layer and an outer layer from the inside to the outside; the chemical formula of the core layer is: Na x1 [Li y1 (Ni a1 Fe b1 Mn c1 ) z1 ]O2 formula I; 0.8≤x1<0.85, 0≤y1≤0.05, 0.9≤z1≤1; y1+z1=1; 0.15≤a1≤0.4; 0.15≤b1≤0.4; 0.4≤c1≤0.8; a1+b1+c1=1; the chemical formula of the intermediate layer is: Na x2 [Li y2 (Ni a2 Fe b2 Mn c2 ) z2 ]O2 formula II; 0.8≤x2<1, 0.03≤y2≤0.07, 0.9≤z2≤1; y2+z2=1; 0.15≤a2≤0.4; 0.15≤b2≤0.4; 0.4≤c2≤0.8; a2+b2+c2=1; the chemical formula of the outer layer is: Na x3 [Li y3 (Ni a3 Fe b3 Mn c3 ) z3]O2 0.8≤x3<1, 0.05≤y3≤0.1, 0.9≤z3≤1; y3+z3=1; 0.15≤a3≤0.4; 0.15≤b3≤0.4; 0.4≤c3≤0.8; a3+b3+c3=1. The positive electrode material in the present invention has a multi-layer structure with a gradient from the inside to the outside. The inner core is sintered at a low temperature to form a compact core structure with few defects, which can improve the compressive resistance of the material; the middle layer is sintered at a high temperature, and the solid phase reaction between the particles forms a stable crystal form. By controlling the time to control the grain size, the production of positive electrodes with the required grain size can be achieved. The third layer, i.e., the outermost particle surface layer, is supplemented with lithium salt and sodium salt, and sintered again to improve the initial efficiency and service life of the material.

[0056] In order to further illustrate the present invention, a sodium ion positive electrode material capable of achieving rapid charge and discharge, a preparation method thereof, and a sodium ion battery provided by the present invention are described in detail below in conjunction with embodiments, but it should not be construed as limiting the scope of protection of the present invention.

[0057] Example 1

[0058] 1. Mix the raw materials sodium hydroxide, lithium hydroxide, nickel hydroxide, manganese hydroxide and ferric sulfate according to Na 0.8 [Li 0.02 (Ni 0.25 Fe 0.25 Mn 0.5 ) 0.98 ]O2 molar ratio is mixed evenly;

[0059] 2. Sinter the mixture at 490°C for 5 hours under nitrogen atmosphere to obtain a core, and cool the mixture to less than 250°C;

[0060] 3. Add appropriate amount of sodium oxide, lithium hydroxide, nickel hydroxide, manganese hydroxide and ferric sulfate into the mixture and stir evenly. The theoretical chemical formula is about Na 0.85 [Li 0.05 (Ni 0.3 Fe 0.22 Mn 0.48 ) 0.95 ]O2;

[0061] 4. Secondary sintering: under the protection of nitrogen atmosphere, stir and sinter at a temperature of 1000°C for 5 hours to form an intermediate layer, and cool the mixture to less than 250°C;

[0062] 5. Add sodium oxide, lithium hydroxide, nickel hydroxide, manganese hydroxide, and ferric sulfate, and granulate according to demand; the theoretical chemical formula is about Na 0.85 [Li 0.08 (Ni 0.25 Fe 0.25 Mn 0.5 )0.92 ]O2

[0063] 6. Sinter three times at 800°C under nitrogen atmosphere for 2 hours. After cooling, shape and screen to obtain the positive electrode material.

[0064] Example 2

[0065] 1. Mix the raw materials sodium acetate, lithium acetate, nickel hydroxide, manganese hydroxide and ferric chloride according to Na 0.8 [Li 0.02 (Ni 0.25 Fe 0.25 Mn 0.5 ) 0.98 ]O2 molar ratio is mixed evenly;

[0066] 2. Sinter the mixture at 350°C for 6 hours under nitrogen atmosphere to obtain a core, and cool the mixture to less than 250°C;

[0067] 3. Add appropriate amount of sodium acetate, lithium acetate, nickel hydroxide, manganese hydroxide, and ferric chloride into the mixture and stir evenly. The theoretical chemical formula is about Na 0.85 [Li 0.05 (Ni 0.3 Fe 0.22 Mn 0.48 ) 0.95 ]O2;

[0068] 4. Secondary sintering: under the protection of nitrogen atmosphere, stirring and sintering temperature is 700℃, sintering time is 8h, forming an intermediate layer, and the mixture is cooled to less than 250℃;

[0069] 5. Add sodium acetate, lithium acetate, nickel hydroxide, manganese hydroxide, and ferric chloride, and granulate according to demand; the theoretical chemical formula is about Na 0.85 [Li 0.08 (Ni 0.25 Fe 0.25 Mn 0.5 ) 0.92 ]O2

[0070] 6. Sinter three times at 600°C under nitrogen atmosphere for 2 hours. After cooling, shape and screen to obtain the positive electrode material.

[0071] Example 3

[0072] 1. Mix the raw materials sodium acetate, lithium acetate, nickel carbonate, manganese carbonate and ferric chloride according to Na 0.8 [Li 0.02 (Ni 0.25 Fe 0.25 Mn 0.5 ) 0.98 ]O2 molar ratio is mixed evenly;

[0073] 2. Sinter the mixture at 400°C for 5 hours under nitrogen atmosphere to obtain a core, and cool the mixture to less than 250°C;

[0074] 3. Add appropriate amount of sodium acetate, lithium acetate, nickel carbonate, manganese carbonate, and ferric chloride into the mixture and stir evenly. The theoretical chemical formula is about Na 0.85 [Li 0.05 (Ni 0.3 Fe 0.22 Mn 0.48 ) 0.95 ]O2;

[0075] 4. Secondary sintering: under nitrogen atmosphere protection, stirring and sintering temperature is 750℃, sintering time is 10h, forming an intermediate layer, and the mixture is cooled to less than 250℃;

[0076] 5. Add sodium acetate, lithium acetate, nickel carbonate, manganese carbonate, and ferric chloride, and granulate according to demand; the theoretical chemical formula is about Na 0.85 [Li 0.08 (Ni 0.25 Fe 0.25 Mn 0.5 ) 0.92 ]O2

[0077] 6. Sinter three times at 600°C under nitrogen atmosphere for 3 hours. After cooling, shape and screen to obtain the positive electrode material.

[0078] The positive electrode materials obtained in Examples 1 to 3 were dried at 85° C. for 4 h, ground and passed through a 100-mesh sieve.

[0079] The cathode material: conductive carbon black: CNT: PVDF = 90: 2.5: 2.5: 5 were mixed to form a pole piece, and the size of the pole piece was close to 10mm×10mm. The pole piece was baked at 120℃ in vacuum for 12 hours and then put into the glove box for standby. The Na half-cell was tested. The results are shown in Table 1.

[0080] Table 1 Electrochemical performance of sodium ion batteries in Examples 1 to 3 of the present invention

[0081]

[0082] Application Examples

[0083] 1) Preparation of positive electrode sheet: The positive electrode materials in Example 1: conductive carbon black: CNT: PVDF = 90: 2.5: 2.5: 5 are mixed to form a sheet, and then cut into a circular sheet with a diameter of 14 mm after drying, and weighed. The sheet is placed in a vacuum oven and dried for 12 hours to remove residual NMP and moisture; after being taken out, it is immediately transferred to a glove box for standby use.

[0084] The negative electrode uses a sodium sheet, the separator uses a 16μm PE film, the electrolyte uses 1M Na PF6 EC / DMC=1:1, and a half-cell is prepared for charge and discharge curve testing. Figure 1 is the charge and discharge curve of the sodium ion battery obtained in Example 1 of the present invention under 0.2C conditions, Figure 1 It can be seen that the product's first charging capacity is 144.2mAh / g, the first discharge capacity is 123mAh / g, and the first efficiency is 85.3%. The product has a high first efficiency and the discharge capacity meets expectations.

[0085] 2) The positive electrode, separator, and electrolyte are the same as the half-cell in 1);

[0086] Preparation of negative electrode sheet: According to the negative electrode material: SP: CMC: SBR = 95.9: 1: 1.1: 2, deionized water is used as a dispersant to mix well and then the slurry is coated on aluminum foil; after drying, it is cut into circular electrode sheets with a diameter of 16 mm and weighed (NP ratio or CB value is designed according to 1.15, that is, the negative electrode is 15% excessive); the electrode sheet is placed in a vacuum oven for 8 hours to remove residual moisture; after taking it out, it is immediately transferred to the glove box for standby. The full battery is tested for cycle performance.

[0087] Figure 2 is the cycle curve of the sodium ion battery obtained in Example 1 of the present invention, Figure 2 It can be seen that the capacity retention rate after 300 cycles is greater than 85%, and the material has an excellent cycle life.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A sodium ion positive electrode material capable of rapid charge and discharge, having a multilayer structure, which comprises a core layer, an intermediate layer and an outer layer from the inside to the outside; The chemical formula of the core layer is: Na x1 [Li y1 (Ni a1 Fe b1 Mn c1 ) z1 ]O2 formula I; 0.8≤x1<0.85, 0≤y1≤0.02, 0.95≤z1≤1; y1+z1=1; 0.15≤a1≤0.4; 0.15≤b1≤0.4; 0.4≤c1≤0.8; a1+b1+c1=1; The chemical formula of the intermediate layer is: Na x2 [Li y2 (Ni a2 Fe b2 Mn c2 ) z2 ]O2 formula II; 0.8≤x2<1, 0.03≤y2≤0.05, 0.93≤z2≤0.97; y2+z2=1; 0.15≤a2≤0.4; 0.15≤b2≤0.4; 0.4≤c2≤0.8; a2+b2+c2=1; The chemical formula of the outer layer is: Na x3 [Li y3 (Ni a3 Fe b3 Mn c3 ) z3 ]O2 Formula III; 0.8≤x3<1, 0.05<y3≤0.1, 0.9≤z3≤0.95; y3+z3=1; 0.15≤a3≤0.4; 0.15≤b3≤0.4; 0.4≤c3≤0.8; a3+b3+c3=1; The core layer is sintered at a low temperature of 200-500°C and for 5-10 hours. The intermediate layer is sintered at a high temperature of 600-1500°C for 2-10 hours. The sintering temperature of the outer layer is 500-1000° C., and the sintering time is 3-8 hours.

2. The sodium ion positive electrode material capable of rapid charge and discharge according to claim 1, characterized in that: The sodium ion positive electrode material capable of achieving rapid charge and discharge is an O3 phase material.

3. The sodium ion positive electrode material capable of rapid charge and discharge according to claim 1, characterized in that: The sodium ion positive electrode material capable of achieving rapid charge and discharge has a chemical formula shown in Formula IV: Na x [Li y (Ni a Fe b Mn c ) z O₂ formula IV; Among them, 0.8≤X<1; y≤0.1; 0.9≤z≤1; y+z=1; 0.15≤a≤0.4; 0.15≤b≤0.4; 0.4≤c≤0.8; a+b+c=1.

4. The method for preparing a sodium ion positive electrode material capable of rapid charge and discharge according to claim 1, comprising the following steps: A) Sodium source, lithium source, nickel source, iron source and manganese source are placed according to Na x1 [Li y1 (Ni a1 Fe b1 Mn c1 ) z1 ] The stoichiometric ratio of the raw materials is uniformly mixed in O2, and a sintering is performed under a protective atmosphere to obtain a core layer; B) According to Na x2 [Li y2 (Ni a2 Fe b2 Mn c2 ) z2 ]O2 is added with a sodium source, a lithium source, a nickel source, an iron source and a manganese source in a stoichiometric ratio, and secondary sintering is performed under a protective atmosphere to obtain an intermediate layer; C) According to Na x3 [Li y3 (Ni a3 Fe b3 Mn c3 ) z3 ]A sodium source, a lithium source, a nickel source, an iron source and a manganese source are added in a stoichiometric ratio of O2, and sintered three times under a protective atmosphere to obtain a sodium ion positive electrode material that can achieve fast charge and discharge.

5. The preparation method according to claim 4, characterized in that: The sodium source is one or more of sodium hydroxide, sodium carbonate, sodium chloride, sodium sulfate, sodium nitrate and sodium acetate; The lithium source is one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium sulfate, lithium nitrate and lithium acetate; The nickel source is one or more of nickel hydroxide, nickel carbonate, nickel sulfate, nickel nitrate, nickel acetate, and nickel oxalate; The iron source is one or more of iron powder, ferric chloride, ferric nitrate, ferric sulfate, ferric oxide, and ferrous oxide; The manganese source is one or more of manganese hydroxide, manganese carbonate, manganese sulfate, manganese nitrate, manganese acetate and manganese oxalate.

6. The preparation method according to claim 4, characterized in that: The protective atmosphere is one or more of nitrogen, helium and argon.

7. A sodium ion battery, comprising the sodium ion positive electrode material capable of rapid charge and discharge as described in any one of claims 1 to 3 or the sodium ion positive electrode material capable of rapid charge and discharge obtained by the preparation method as described in any one of claims 4 to 6.